Specifications for Innovative, Enabling Biomaterials Based on the Principles of Biocompatibility Mechanisms - Williams, David F. (Frontiers in Bioengineering and Biotechnology, 2019)
In any engineering discipline, whenever products are designed, manufactured and ultimately utilized for the benefits of society, a series of specifications for the product are defined, and maybe refined, in order that they perform as effectively as possible, with due attention being paid to the safety and economic aspects. These specifications are established with respect to all of the relevant properties, including those determined by mechanical, physical, chemical, manufacturing and environmental conditions, and the resulting design and materials selection reflects the optimal balance. In areas of medical technology, these specifications should be based on both functionality, which determines whether a device can actually perform as intended, and biocompatibility, which determines how the device interacts, both acutely and chronically, with the body. Unfortunately, whilst so much progress has been made with the development of superior functionality for the treatment and diagnosis of so many disease states, this is not the same for biocompatibility, where the single most-important currently adopted specification is that the device should do no harm, which falls far short of the ideal requirement. This paper addresses the profound need for biomaterials specifications to be based on the mechanisms of biocompatibility.